HCA Holdings, Inc. : for-profit medicine and unnecessary surgery - Nielsen, Sister Petra (Catherine); Spellane, Patrick; Wang, Zhi; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On August 6, 2012, HCA Holdings, Inc., one of the largest for-profit hospital management companies in America, revealed to investors that the U.S. Attorneys Office in Miami had requested documents related to unnecessary cardiac procedures at ten of its hospitals. HCA's announcement coincided with an article published by The New York Times on the investigation. HCA is the largest hospital management company in America and has had a history of legal issues ranging from Medicare fraud to unnecessary heart procedures.
Originally published in Nielsen, P., Spellane, P., Wang, W., & ORourke, J. S. (2012). HCA Holdings, Inc.: For-profit medicine and unnecessary surgery. 12-10. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; HCA (Firm); Hospital management companies -- United States; Hospitals, Proprietary -- United States; Surgery, Unnecessary -- United States